SUCCESS FACTORS FOR ONLINE ADULT EDUCATION (The Journal of Psychology and Sociology, 2023)
The study is aimed to identify the success factors of online learning for adult learners who are Master Degree students of universities at the profile and scientific-pedagogical directions. Quantitative and qualitative data collection methods were used, respectively - an online survey and semi-structured online interviews. The study involved Master Degree students aged 25 years and older from 5 regions of the country. A literature review on this issue showed that educational, human, institutional and technological factors and components of successful online learning are distinguished in modern online learning. The data obtained were analyzed in line with the indicated critical factors with information coding and using the content analysis method. The following critical factors for the success of online learning for adult learners have been identified: a sustainable online learning environment, the developed and customized learning management system (LMS), the number and volume of credits, the content quality-availability-attractiveness, competent assessment, the correspondence between learning objectives and expectations of learners, organizational communications and support, opportunities for social interactions. It was revealed that staying in a sustainable online learning environment and the quality of content are the most important factors for the success of online learning for adult learners.Key words: Online learning, adult learning, graduate students, online learning success factors.